Comparação da rigidez arterial central e da morfologia da onda de pulso, durante o envelhecimento, em indivíduos idosos e muito idosos. - Ferreira, Cléria Rodrigues (2021)
Introduction: In recent years, the population's life expectancy has increased considerably. Vascular aging is determined by changes in the elastic properties of arterial vessels. Central arterial stiffness (CAR) increases with aging, due to cellular changes in the arterial wall, in addition to being related to cardiovascular risk (CVR) and is an important finding in elderly and very elderly patients. Objectives: to compare central arterial stiffness and pulse wave morphology in elderly and very elderly individuals. Materials and methods: This is a cross-sectional study in which we selected 932 patients grouped into six age groups, as follows: FE-1: ≥60 and <65 years (n=69); FE-2: ≥65 and <70 years (n=309); FE-3:≥70 and <75 years (n=247); FE-4: ≥ 75 and <80 years (n=155); FE-5: ≥80 and <85 years (n=97) and FE-6: ≥85 years (n=55). All groups were submitted to applanation tonometry (TA) in which the carotid-femoral pulse wave velocity (cf-PWV) was measured and the morphologies of the arterial pulse waves recorded. The clinical and hemodynamic data of the patients, obtained during a single outpatient visit, were evaluated, and those patients in whom TA and Pulse Wave Morphology (MOP) data were simultaneously measured were selected. If there was more than one outpatient visit, in which such measurements were performed simultaneously, the first visit is the one selected. For statistical analysis, Shapiro Wilk test, Kruskal Wallis and linear regression for cf-PWV values were performed. Results: A progressive increase in PSb was observed, mainly between FE1 and FE5, as well as an increase in PPb between FE1 and FE6. There was a progressive increase in cf-PWV up to 75 years of age, in which we observed the existence of a plateau that extended to the following age groups. The same behavior was observed for the morphology of the pulse wave, as there was an increase in the AP, ejector and reflection waves. Conclusion: Central arterial stiffness and morphological changes in the pulse wave, present in very elderly patients (over 80 years), are already noticed with the same intensity in elderly patients over 75 years.